Redescription of Allobates brunneus (Cope) 1887 (Anura: Aromobatidae: Allobatinae), with a description of the tadpole, call, and reproductive behavior - Lima, Albertina P.; Caldwell, Janalee P.; Strussmann, Christine (Zootaxa, 2009)
Allobates brunneus, long known as Colostethus brunneus, was originally described by E. D. Cope in 1887. Specimens on which the original description was based were collected by H. H. Smith from the village of Chapada dos Guimarães, in the state of Mato Grosso, Brazil. Because of the brevity of the original description, new material of this species was collected from 1998–2001 for a redescription. In recent years, numerous undescribed species of Allobates have been identified throughout the Amazon region. Our redescription of A. brunneus includes many characters not given in the original description that are necessary to distinguish this species from other similar ones. We also include descriptions of the tadpole and vocalization. Allobates brunneus is a small frog, in which males range in snout–vent length from 14.8–18.3 mm, and females from 15.8–19.8 mm. The species typically inhabits swamp forests along small streams or rivers. Although the frog was once abundant, the construction of a hydroelectric dam and reservoir on the Rio Manso has inundated many of the localities where it was formerly known, greatly reducing the number of known populations.